Cardiomyopathy and echocardiographic abnormalities in Indian patients with psoriasis: Results of a pilot study. Issue 3 (9th November 2020) - Rana, Ashwani; Mahajan, Vikram K.; Mehta, Karaninder S.; Chauhan, Pushpinder S.; Kumar, Mukul; Sharma, Anuj; Sharma, Reena; Dhattarwal, Niharika; Sondhi, Megha
Abstract: Background: The relationship between psoriasis and cardiomyopathy is understudied in Indian patients. Objective: We evaluated psoriasis patients for cardiomyopathy and other echocardiographic abnormalities. Methods: About 98 (M:F = 67:31) patients with mild to moderate psoriasis aged 18‐75 years (mean ± SD = 42.12 ± 12.79 years) having no pre‐existing metabolic syndrome and cardiovascular disorders were studied. X‐ray chest, electrocardiogram and echocardiography were performed and interpreted by cardiologist for size of the left and right ventricles, left ventricle ejection fraction, diastolic function, pulmonary artery pressure and valve abnormality/regurgitation and their severity as per current guidelines/recommendations. The cardiomyopathies were defined according to standard diagnostic guidelines. Results: Echocardiographic abnormalities were noted in 13 (13.3%) patients aged 19‐75 years (mean ± SD = 43.30 ± 15.71 years). The left ventricular diastolic dysfunction (grade 1) was observed in nine patients (moderate severe psoriasis in four patients) and one of them also had concentric left ventricular hypertrophy; a precursor of restrictive cardiomyopathy. Mild tricuspid valve regurgitation was present in other four patients. There was no statistically significant difference in age, gender, duration and the severity of psoriasis when compared with patients having normal echocardiography. The mitral or aortic valves, pulmonary artery pressure, mid‐right‐ventricular diameter and the left atrial volume showed no abnormality. Conclusions: Psoriasis perhaps plays a role in left ventricular dysfunction and possibly cardiomyopathy even with moderately severe disease and in the absence of clinical symptoms. However, these observations need to be interpreted with caution in the absence of any statistically significant difference between age, gender, duration and severity of psoriasis in the patients having normal and abnormal echocardiography.